A multicentre, randomised, double-blind, placebo controlled study of cryotherapy versus cryotherapy and podophyllotoxin cream as treatment for external anogenital warts. Issue 7 (20th August 2009) - Gilson, R J C; Ross, J; Maw, R; Rowen, D; Sonnex, C; Lacey, C J N
Abstract : Objectives: To compare the efficacy and safety of combination therapy with cryotherapy and podophyllotoxin 0.15% cream versus cryotherapy alone in the treatment of anogenital warts. Methods: A randomised, double-blind, multicentre controlled trial. Patients received podophyllotoxin cream or placebo twice daily for 3 days/week for up to 4 weeks, with weekly cryotherapy continued to week 12 if required. Further treatment from week 12 to 24 was discretionary. Patients were stratified by sex and history of warts. HIV positivity, warts treated in the past 4 months, or warts with a combined area of less than 10 mm 2 were exclusion criteria. Primary endpoints were clearance at weeks 4 and 12. Results: 70 patients per group were randomly assigned and started treatment; 101 first-episode warts, 91 male. No treatment-related serious adverse events were reported. Follow-up at week 12 was 85%. By intention-to-treat analysis, clearances at 4 and 12 weeks were higher in the combination group (60.0% and 60.0%, respectively) than with cryotherapy alone (45.7%, 45.7%) although not statistically significant (RR 1.31, 95% CI 0.95to 1.81). By week 24 there was no difference between the groups (68.6% and 64.3%, respectively; RR 1.07, CI 0.84 to 1.35). At week 4, wart clearance was higher in men (p = 0.001) and those with a past history of warts (p = 0.009), but these differences were not detected at week 12. There was some evidence for a higher relapse rate in the group receiving cryotherapy alone. Conclusions: Initial combination therapy with podophyllotoxin/cryotherapy was well tolerated and may have resulted in earlier clearance in some patients, compared with cryotherapy alone; however, overall differences in clearance rates were not statistically significant.